Voice symptoms, dysphagia risk, quality of life, and mental health in total laryngectomized patients: a self-perception study - João Vitor Barbosa Pereira; Vaneli Colombo Rossi; Carlos Takahiro Chone; Ana Carolina Constantini (Brazilian Journal of Otorhinolaryngology, 2025)
Objectives: To establish the sociodemographic profile, identify and relate the presence of voice symptoms, risk for dysphagia, and self-perceived emotional distress, and measure the quality of life of a group of total laryngectomized patients. Method: This is a descriptive, quantitative, cross-sectional study. Subjects aged 18-years and older, of both sexes, who had undergone total laryngectomy. The sample composition was non-probabilistic. A questionnaire was used to obtain sociodemographic data. The perception of voice symptoms was assessed by the Voice Symptom Scale (VoiSS) and the risk of dysphagia was screened using the Eating Assessment Tool (EAT-10). Mental health aspects were measured using the Self-Reporting Questionnaire (SRQ-20) and data on general health, treatment and illness were collected using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core-30 (EORTC QLQ-C30). Results: 12 participants were recruited; mostly male, average age of 64-years. All participants presented voice symptoms and 33% were screened with self-perceived emotional distress and 66.7% progressed with risk for dysphagia; all of them had undergone at least radiotherapy during the treatment. Conclusion: All subjects in the sample had voice symptoms. Risk of dysphagia emerged as a determining factor in the quality of life and mental health of study participants, and was also related to concomitant voice symptoms. In this sample, participants with a high prevalence of voice signs and symptoms were at greater risk of emotional distress.